E-training management system for UiTM Terengganu lecturer (E-TRaiMS) / Fakhrulrazi Ibrahim - Ibrahim, Fakhrulrazi (2014)
Nowadays, in managing training and reports by iLQAM UiTM Terengganu still use manually where management needs to fill out lots of papers and will be stored into the manual file system. Therefore, E-Training Management System for iLQAM UiTM Terengganu (E-TraiMS) is web-based system technology where management becomes easier, faster and more efficiently to manage training and reports. In this way, flexible features can support multiple users allowing them to create and join trainings also easy to generating reports through this system. Agile Unified Process (AUP) methodology is used in order to help in developing this system. This methodology consists of 4 phases which consist of Inception, Elaboration, Construction and Transition phase. The evaluation conducted based on the questionnaires given to 10 respondents which consist of iLQAM staff and lecturers to evaluate the system. It is found that the system is able to use based on the result that evaluated through on the user interface, usefulness, ease of use, ease of learning, and satisfaction by set of questionnaire. The result of evaluation, most of respondent satisfied with the system and believes can be improved time by time. Based on respondent analysis, showed that the highest mean based on user feedback is item satisfaction (Mean=4.6, SD=0.516). As a conclusion, this E-TraiMS system give more benefits for the users and hopefully will contribute further in this evolving for better training management system.